Determination of insecticide Deltamethrin residues in local and imported raw milk samples collected from different animal’s species and the effect of processing heat treatment on its content in milk: Sara Ahmed Abd Al-Zahra and Najim Hadi Najim - Al-Zahra, Sara Ahmed Abd (The Iraqi Journal of Veterinary Medicine, 2017)
A total of 163 milk samples (500 ml each) of cows, ewe, goats, buffaloes, camels were collected randomly at weekly intervals (10 samples/ week) from both Abu-Ghraib and Al-Fudhailiya villages and also for different local retail markets inside the Baghdad province and these samples were including milk of different animal species, milk cans, bulk milk tanks and imported Ultra-high temperature processing milk. Among the total milk samples only 138 milk samples were examined during two climatic periods where the first period was in summer that extended from the beginning of September to the end of October 2015 while the second period was in winter that extended from the beginning of January to the end of February 2016. Besides that, some of the selected positive samples for Deltametrin residues were subjected to one of the commercial heat treatments such as 63°C/30 min., 80°C/5 min. and 100°C/5 min. to evaluate the efficiency of heat exposure on the degradation of Deltametrin residues in milk. The results pointed out that milk samples containing the higher fat percentage exhibited significantly (P<0.05) the highest concentration of Deltametrin in summer (0.08ppm) than in winter (0.008 ppm) seasons. It was clearly obvious that the detectable concentrations of the Deltametrin were higher in buffalo’s and ewe milk samples than those found in cows, goats and camels and such results could be attributed to the higher fat content of buffalos and ewes milk than the other animals as well as the lipophilic nature of the Deltamethrin. In other word, increased the fat percentages of milk was being associated with an increased level of Deltametrin residues due to the lipophilic nature of the Deltametrin pesticide. The current results revealed that milk samples that were collected from buffaloes, ewes and cows recorded significantly (P<0.05) the highest Deltametrin residues in summer season where their mean levels that exceeded the accepted MRLs of 0.05 ppm to milk samples of goats and camels that had significantly (P<0.05) the lowest mean levels of Deltametrin residues where their means levels were 0.038 and 0.032 ppm respectively. There was a significant (P<0.05) seasonal variation of the Deltametrin concentrations in milk samples for each animal species where all the milk samples that were collected from buffaloes, ewe, cows, goats and camels had significantly (P<0.05) higher mean levels of Deltametrin residues in summer season than in winter season, milk samples that were collected from milk cans (5, 25 and 50 kg) recorded significantly (P<0.05). The highest Deltametrin residues during the summer season in comparison to 10 tons bulk milk tank samples.